Religious Spirituality and Family Resilience: The Contribution of Kyai in Building the Social Resilience of Muslim Families - Safithri, Awaliya; Sumbulah, Umi; Fadil, Fadil (Al Irsyad: Jurnal Studi Islam, 2026)
This study is based on the still-limited body of scholarly research that specifically examines the role of kyai in strengthening santri family resilience, grounded in the maq??id al-sharia, within pesantren environments in a comprehensive and in-depth manner. This research aims to analyze KH's thoughts, roles, and impacts. Yazid Karimullah is strengthening the resilience of santri families. The method used is a descriptive qualitative approach to gain an in-depth understanding of the kyai contributions to santri family resilience at Pesantren Nurul Qarnain Jember through interviews, observations, documentation, and systematic thematic analysis. The results show that family resilience according to KH. Yazid Karimullah is built on the principles of al-amna (security), ash-shihah (health), and al-kifayah (sufficiency), which complement each other in creating harmonious and sustainable families. This resilience is strengthened by religious, ethical, and moral values, resulting in sakinah, mawaddah, wa rahmah (tranquil, loving, and merciful) families. Various strategies are implemented, such as the establishment of ISNUQ, integration of marriage education into the curriculum, family counseling, conflict mediation, economic empowerment, religious sermons, and the prohibition of unregistered marriage (nikah sirri), early marriage, and domestic violence. These findings demonstrate the comprehensive implementation of maq??id al-sharia and the role of kyai as social agents who shape strong, independent, and adaptive santri families in facing modern challenges. The conclusion of this study is that santri family resilience is formed through the integration of religious values, pesantren strategies, and the kyai’s role as a social agent. The significance of this research enriches the study of maq??id al-sharia and provides practical contributions for pesantren in strengthening santri family resilience.